O gênero Borreria (Spermacoceae, Rubiaceae) no estado do Ceará, Brasil - Almeida Nepomuceno, Francisco Alvaro (2018)
This work comprises the taxonomic treatment of genus Borreria for the Ceará flora. Based on field observations and herbaria specimens, eleven species were recorded: Borreria apodiensis, B. brownii, B. capitata, B. cupularis, B. latifolia, B. ocymifolia, B. scabiosoides, B. spinosa, B. tenella, B. verticillata and B. virgata. Most species occur in Caatinga vegetation and nine were registered in environmental conservation units. B. brownii, B. spinosa and B. verticillata are widely spread throughout the phytoecological units of the state. Four species have a more restricted occurrence in Ceará: B. capitata and B. cupularis (in the Araripe Plateau), B. tenella (in the Ubatuba Mountains and adjacent areas) and B. virgata (in the Ibiapaba Plateau). On the other hand, B. apodiensis is a endemic species to the Brazil, that is restricted to Chapada do Apodi. An identification key, descriptions, images, geographic distribution and habitat of the species are provided.